Perceptions of the effectiveness of the Master of Science in Nursing program at Tennessee State University as reported by the graduates of the program. - Temple ER (Perceptions of the Effectiveness of the Master of Science in Nursing Program at Tennessee State University as Reported by the Graduates of the Program, 2003)
The purpose of this study was to provide an analysis of the perceptions of the effectiveness of the graduate nursing program at Tennessee State University as reported by the graduates of the program. The study also provided a demographic summary of the graduates and revealed the student's perceptions of their advanced nursing degree.To date the Master of Science in Nursing (MSN) program at Tennessee State University is the most recently approved and only state supported masters in nursing program in Middle Tennessee. The first class graduated in 1996 through and including the class of 2002. 70 nurses have graduated from the program to date. Graduates from the program were asked to participate in the study and were sent questionnaires. Fifty-two graduates provided essential data with the Graduate Nurses Survey. Three hypotheses were analyzed by descriptive and inferential statistical methods. The reported level of satisfaction with the graduate Nursing Program curriculum and current employment performance received high levels of satisfaction with their preparation from the program. Graduates from the program are employed on a full time basis and reported that a master's degree as required for their current position. The majority of the MSN alumni are willing to recommend the program to their colleagues.